Bacillus subtilis RarA Acts as a Positive RecA Accessory Protein - Romero, Hector; Serrano, Ester; Hernández-Tamayo, Rogelio; Carrasco, Begoña; Cárdenas, Paula P.; Ayora, Silvia; Graumann, Peter L.; Alonso, Juan C. (Frontiers in Microbiology, 2020)
UUbiquitous RarA AAA+ ATPases play crucial roles in the cellular response to blocked replication forks in pro- and eukaryotes. Here, we provide evidence that absence of RarA reduced the viability of recA, recO and recF15 cells during unperturbed growth. The rarA gene was epistatic to recO and recF genes in response to H2O2- or MMS-induced DNA damage. Conversely, the inactivation of rarA partially suppressed the HR defect of mutants lacking end-resection (addAB, recJ, recQ, recS) or branch migration (ruvAB, recG, radA) activity. RarA contributes to RecA thread formation, that are thought to be the active forms of RecA during homology search. The absence of RarA reduced RecA accumulation, and the formation of visible RecA threads in vivo upon DNA damage. When rarA was combined with mutations in genuine RecA accessory genes, RecA accumulation was further reduced in rarA recU and rarA recX double mutant cells, and was blocked in rarA recF15 cells. These results suggest that RarA contributes to the assembly of RecA nucleoprotein filaments onto single-stranded DNA, and possibly antagonizes RecA filament disassembly